DoD-Supported Overseas Training Rotations in Tropical Medicine and Global Health, 2000–2015. Issue 3 (1st March 2017) - Mancuso, James D.; Hickey, Patrick W.; Coldren, Rodney L.; Korman, Amy K.; Keep, Lisa W.; DeFraites, Robert F.; Smith, Maria; Mancuso, Luke J.; Sanchez, Jose L.
ABSTRACT: In 1999, the Department of Defense developed a tropical medicine training program (TMTP) to train military physicians, medical students, and scientists in performing surveillance activities in an overseas environment. This review describes the competencies, educational approach, program participants, institutional collaborations, and process outcomes of the TMTP from 2000 to 2015. TMTP-sponsored rotations addressed a wide variety of interdisciplinary competencies, many of which have military-unique applications. Rotations consisted of both didactic and experiential (overseas) components. The program provided 282 rotations for 260 trainees between 2006 and 2015, the years for which data were available. The Department of Defense accrues benefits from this training program in three main ways: (1) building a cadre of health care professionals who will go on to work at the overseas research laboratories, (2) supporting force health protection and readiness through experiential tropical medicine training, and (3) engaging in global health collaborations and partnerships. The primary challenges include funding, health and security, trainee and site heterogeneity, supervision, trainee engagement, and burden on the host institution. The program will continue to focus on improvement in these areas, with special attention to trainee preparation, communication with both trainees and host sites, and increasing reciprocity with host sites and their faculty.